Kepemimpinan Transformasional Kepala Madrasah Dalam Membangun Karakter Siswa Di Mi Ma’arif Bego Depok Sleman - Wawan Hadi Santoso (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2018)
The background of this research originated from moral decline that occurs in society today. One place of character building is in educational institutions or schools. Therefore required a leader who has the ability to qualify for the formation of character in school successfully. One of the necessary forms of leadership is transformational leadership. The data is analyzed and tested its validity through triangulation of data based on source and method, so that can be drawn a conclusion. The result of this research shows that the head of the madrasah has a transformational leader attitude. First, idealized influence, inspiration motivation, intellectual and individual consideration. The impact of the transformational leadership of Madrasah headmasters in MI Ma'arif Bego Depok Sleman towards the character of the students is the harmony among the madrasahs, the condition of the clean, beautiful and comfortable madrasah environment and the madrasah is growing. The supporting factors of success are education and personal character of madrasah head, adequate facilities, parent role, teacher and competent employee, and supportive madrasah environment. Conversely, the inhibiting factor is the proximity of madrasah heads with madrasahs, some facilities and infrastructure need attention, discipline of teachers and madrasah employees and the number of madrasah students.